Procesos de comercialización de productos de la Empresa Castillo Lab S.A. - Castillo Caicedo, Cesar Guillermo (2021)
The company Castillo Lab S.A., has the function of designing, assembling, manufacturing and marketing internal computer devices such as hard drives, memories, heat sinks, liquid cooling systems, among others. The commercialization of goods or services is of great importance for the success of most companies, so the directors, managers or bosses must put emphasis on the effective development of this activity, however many organizations have problems when complying with the objectives related to the promotion and sale of the products, which causes difficulty in obtaining higher income, better acceptance of the people, that the companies are recognized at the local or national level and above all that the products meet the needs of the customers. The idea is for Castillo Lab to overcome all these inconveniences and thus improve the commercialization processes of products and services that this company offers.